Recommendations for the inspection, maintenance and management of car park structures (Thomas Telford, 2002)
Most multi-storey car parks are constructed of reinforced concrete, to normal building standards. However, severe environments and poor repair mean many have suffered from early deterioration, structural defects and safety shortcomings. This guide provides recommendations for good practice.
At foot of title: ICE.
Keywords: Parking facilities -- Maintenance and repair.; elektronické knihy; electronic books